Epidemiology of Primary Sjögren's Syndrome in a French Multiracial/Multiethnic Area. Issue 3 (March 2014) - Maldini, Carla; Seror, Raphaèle; Fain, Olivier; Dhote, Robin; Amoura, Zahir; De, Michel; Delassus, Jean‐Luc; Falgarone, Géraldine; Guillevin, Loïc; Le Guern, Véronique; Lhote, François; Meyer, Olivier; et al.
<x xml:space="preserve">Abstract</x> Objective To describe the epidemiology of primary Sjögren's syndrome (SS) in a multiracial/multiethnic population. Methods A cross‐sectional study with 5 case‐retrieval sources identified adults with primary SS living in the Greater Paris area (population 1, 172, 482 adults) in 2007. Diagnoses were verified by the American–European Consensus Group (AECG) criteria and study‐specific enlarged criteria based on the presence of ≥3 of 4 AECG items among subjective oral or ocular dryness, anti‐SSA/SSB positivity, and positive minor salivary gland biopsy results. Prevalence estimates were standardized to those for the world population and a 5‐source capture–recapture analysis (CRA) was used. Racial/ethnic differences in primary SS features were evaluated. Results In all, 133 subjects met the AECG criteria and 203 met the enlarged criteria. The 2007 prevalence of primary SS was 1.02 cases per 10, 000 adults (95% confidence interval [95% CI] 0.85–1.22) for the AECG criteria and 1.52 cases per 10, 000 adults (95% CI 1.30–1.76) for the enlarged criteria. The CRA indicated completeness of case findings of ∼90%. Compared to subjects with European backgrounds, those with non‐European backgrounds had 2.1–2.3 times higher primary SS prevalence and were younger (P < 0.0001) and were more likely to have polyclonal hypergammaglobulinemia (P < 0.0001) and anti‐SSA/SSB antibodies (P = 0.0005 and P < 0.0001 for the AECG and enlarged criteria, respectively). Conclusion The figure of 1.02–1.52 cases per 10, 000 adults we found and estimates from the few other population‐based census surveys support that the prevalence of diagnosed primary SS is between 1 and 9 cases per 10, 000 people (0.01–0.9%) in the general population. Non‐European race/ethnicity may be associated with increased primary SS risk and a distinct disease profile.